Awareness About Mosquito Borne Diseases in Community and Stakeholders in Urban Slums of Agra district - Singh, Viresh Kunver; Agrawal, Renu; Singh, Geetu (Indian Journal of Community Health, 2021)
Background: Mosquito borne diseases of public health importance are complex. These diseases are important causes of morbidity and mortality. Objective: To determine the knowledge and determinants about MBDs in community and stakeholders among slum dwellers of Agra. Materials and Methods: A community based cross sectional study was conducted in urban slums of Agra city. A sample size of 400 participants and 100 stakeholders from Municipal Corporation, health department, community leaders and community representatives were interviewed. Results: Maximum participants were of age group 26-35 years (23.5%) followed by 36-45 years (21.5%), of those 57.25% and 42.75% were men and women respectively. Most of participants (96.75%) did not have any knowledge about types or names of mosquitoes (Aedes, Anopheles and Culex). More than 50% of participants reported that MBDs spreads through bite of infected mosquitoes followed by poor environmental hygiene (34.75%). Almost all stakeholders (98.0%) had knowledge about name of mosquitoes. 80% of stakeholders perceived their responsibility towards MBD prevention and control. Conclusion: Knowledge about mosquito borne diseases ranged from only 3% aware about types of mosquito, around 50% aware of breeding and habitats of mosquitoes with poor knowledge of larvae. Stakeholders had better awareness than community.